Diagnóstico e avaliação de coleta e disposição de lodo de fossa e de tanque séptico em Cuiabá - MT - Ramos, Lediane Léslie Campos (2014)
Due to insecurity and lack of public collector sewer in the city of Cuiabá is great demand for the services of clean fossa companies, which becomes a problem, since the sludge generated by septic tank systems entails significant concentrations of nutrients, organic matter, inorganic pollutants and pathogenic organisms. The present study aims at the diagnosis and evaluation of the final destination of the sludge pit and septic tank in Cuiabá / MT, and proposes measures of adequacy of treatment. For this survey interviews were held with the companies providing this service, and with the Tijucal Sewage Treatment Station (ETE Tijucal). The station consists of preliminary treatment (sandbox, railing and Parshall), two UASB, anaerobic pond, facultative pond followed by two in parallel, and a maturation pond. Your current treatment capacity is 50 L / s, but receives a daily flow of 56.23 L / s. Surveys conducted in this paper indicates that the daily flow received may be higher than that presented by the company responsible for the management of ETE. Besides quantifying the volume of sludge released daily characterization was carried out by determining the following parameters: pH, temperature, alkalinity, total Total solids, volatile solids, fixed solids, settleable solids, oils and grease, BOD, COD, Total Phosphorus, Nitrogen Kjeldahl. According to the results of the characterization and comparison with studies conducted in this research identified a possible treatment system for the sludge pits and septic tanks.